September the 11th 2001 and security dilemma. - Soltani, Fakhreddin; Jawan, Jayum; Ahmad, Zaid (Canadian Academy of Oriental and Occidental Culture, 2010)
Security and insecurity are complex concepts that states have problem in defining them in different conditions. Complexity of the concepts comes out of security dilemma which states face when they seek to recognize enemy and scale of threat that the enemy may cause. Events of September the 11th formed a new condition in which United States faced the security dilemma that had not risen from a specific country but the enemy that was not recognizable and did not behave like states. United States attempted to solve the mentioned security dilemma by defining enemy, its threats and the new condition after events of September the 11th. This article, in order to explain the security dilemma of the United States after events of the September the 11th, is written in two parts; the first part is to explain security dilemma and the approaches that have been given to solve it and the second part tends to explain the security dilemma that United States faced after terrorist attacks of September the 11th 2001.